Applying Dependency Injection Through AOP Programming to Analyze the Performance of OS - Arora, Jatin; Sidhu, Jagandeep Singh; Kaur, Pavneet (International Journal of Computer Sciences and Engineering, 2015)
Operating systems are very inflexible towards modification of already existing functionalities such as security, dynamic re-configurability, robustness etc. In such functionalities if need arises for any enhancements then it effects on large fractions of the code. Thus results in difficult to implement. Such functional enhancements in any component of the OS that affect large fractions of the program code, are often called crosscutting concerns. Such cross-cutting concerns can be solved by the new emerging extension to object oriented paradigm i.e. Aspect Oriented Programming (AOP). The main idea in AOP is the programmer’s ability to affect the execution of core code by writing aspects. Aspects are pieces of code that are run before, or after core function for which aspect is written. For example logging is a good example of using aspects. To log all function calls the programmer simply needs to define a logging aspect that is executed before and after each function call in the program. In this work aspects are introduced in the Operating System for implementing various concerns and analyzing the performance based on various metrics.